Anamorphosis of One Day: Historical Time and the 11th December, 1972 - Faria, Daniel (2015)
This article presents a historical narrative of a specific day, December 11th, 1972 and a brief theoretical discussion about the relations between poetics, time and history. The date was selected based on the study of a letter written by Honestino Guimarães, then underground president of Brazil’s National Students Union (UNE), who suffered forced disappearance during the military dictatorship, to his family. The anamorphosis-concept was chosen for this account due to the perception that the narrative strategy needed a better conceptual approach. This work has two main goals: first, to present an experimental historical narrative to the reader, searching for a new way of thinking about contemporary history, more specifically the history of Brazil’s military dictatorship; second, to elaborate some theoretical questions around this experience, bearing in mind not only the experience itself, but also its relations with history writing.